Prospects for agricultural production and food deficits in West Asia and North Africa: the role of high-elevation areas - Oram, Peter (International Food Policy Research Institute, 1988)
This paper was prepared for a meeting held in Ankara in July 1987, sponsored jointly by the Turkish Ministry of Agriculture and the International Center for Agricultural Research in the Dry Areas (!CARDA). A main objective of the meeting was to look at the technical potential for improving the productivity of cereals and food legumes in the high elevation areas that compose almost half of the agricultural land of the main producing countries of West Asia and North Africa (Algeria, Afghanistan, Iran, Iraq, Lebanon, Morocco, Tunisia, Turkey, and the Yemen Arab Republic), as well as important areas of Pakistan, India, Nepal, Mongolia, and China. These upland plateau and mountain areas have a harsh climate, with an abrupt transition from very cold winters (when most of the precipitation occurs) to hot arid summers, and very high variability of precipitation. This restricts the range of crops that can be grown there and increases risk. Because of difficult terrain and remoteness these uplands have remained somewhat isolated from the mainstream of agricultural research and development (especially compared to irrigated land in the plains), and in consequence their production potential has not been fully exploited. The key crops in much of the high elevation land are wheat and pulses, and the meeting explored the measures required to raise their productivity.